Polómetros: linguistic attitudes about the phonetics and morphology of Costa Rican Spanish - Barahona Novoa, Alberto (2018)
In this article, the object of study is the so - called "polómetros", in order to analyze the linguistic attitudes that arouse on the phonetics and morphology of Costa Rican Spanish. These attitudes construct a discrediting and exclusionary speaker profile, which, although not a speaker of a rural area, is identified with him. It reveals, then, the ideological construction around the linguistic change of Costa Rican Spanish.